Trial design and rationale for APOLLO, a Phase 3, placebo-controlled study of patisiran in patients with hereditary ATTR amyloidosis with polyneuropathy - Adams, D. (2017)
Background Patisiran is an investigational RNA interference (RNAi) therapeutic in development for the treatment of hereditary ATTR (hATTR) amyloidosis, a progressive disease associated with significant disability, morbidity, and mortality. Methods Here we describe the rationale and design of the Phase 3 APOLLO study, a randomized, double-blind, placebo-controlled, global study to evaluate the efficacy and safety of patisiran in patients with hATTR amyloidosis with polyneuropathy. Eligible patients are 18–85 years old with hATTR amyloidosis, investigator-estimated survival of ≥2 years, Neuropathy Impairment Score (NIS) of 5–130, and polyneuropathy disability score ≤IIIb. Patients are randomized 2:1 to receive either intravenous patisiran 0.3 mg/kg or placebo once every 3 weeks. The primary objective is to determine the efficacy of patisiran at 18 months based on the difference in the change in modified NIS+7 (a composite measure of motor strength, sensation, reflexes, nerve conduction, and autonomic function) between the patisiran and placebo groups. Secondary objectives are to evaluate the effect of patisiran on Norfolk-Diabetic Neuropathy quality of life questionnaire score, nutritional status (as evaluated by modified body mass index), motor function (as measured by NIS-weakness and timed 10-m walk test), and autonomic symptoms (as measured by the Composite Autonomic Symptom Score-31 questionnaire). Exploratory objectives include assessment of cardiac function and pathologic evaluation to assess nerve fiber innervation and amyloid burden. Safety of patisiran will be assessed throughout the study. Discussion APOLLO represents the largest randomized, Phase 3 study to date in patients with hATTR amyloidosis, with endpoints that capture the multisystemic nature of this disease. .